Variables associated with oral health-related self-efficacy - results of a cross-sectional study - David Bantel; Witold X. Chmielewski; Elmar Brähler; Yve Stöbel-Richter; Markus Zenger; Hendrik Berth (BMC, 2023)
Abstract Background Oral health-related self-efficacy (OH-SE) is pivotal for oral health and is associated with other oral-health related variables, such as dental fear and anxiety (DF/A) and dental hygiene behaviors (DHB). This study attempts to analyze associations between OH-SE and oral healthrelated variables in a German population to extend previous research by analyzing whether OH-SE can be predicted by these variables, as this might contribute to the development of treatment interventions. Methods OH-SE, DF/A, oral health-related quality of life (OHRQoL), self-perceived dental condition, satisfaction with general health, DHB, and socioeconomic status were assessed as a part of the Saxon Longitudinal Study in an adult sample (n = 309, 56.3% female, all Saxon secondary school 8th graders in 1987). The associations of OH-SE with these variables were examined by means of correlation, multiple linear regression analyses, and group comparisons. Significance (p), standardized regression coefficients (β), and effect size (Cohen's d) were calculated. Results The correlation analyses revealed increased OH-SE to be accompanied by low levels of DF/A, high levels of OHRQoL, high levels of self-perceived dental condition, increased satisfaction with general health and socioeconomic status (all r ≥ 0.142; all p ≤ 0.013). In the regression analysis, OH-SE was mainly predicted by self-perceived dental condition and satisfaction with general health (R2 = 0.157) as well as by daily frequency of toothbrushing, OHRQoL, and socioeconomic status on a trend-level basis. In the group comparisons OH-SE was lower in participants with moderate for manifest DF/A and higher in individuals with higher OHRQoL, better self-perceived dental condition, increased satisfaction with general health, increased daily frequency of toothbrushing, more dental appointments, and above-average socioeconomic status (trend level; all t ≥ 1.57; p ≤ 0.059). Conclusions In this cross-sectional study, high levels of OH-SE were mainly predicted by general health as well as self-perceived dental condition. It was also associated with decreased DF/A, increased DHB, higher OHRQoL, and higher socioeconomic status. Future research should analyze these associations in longitudinal designs to address whether interventions focusing on adherence to good DHB improve (dental) health and thus OH-SE. This might be a promising approach, particularly in relation to the treatment of DF/A.